Insect pests of some vegetables grown on small scale with special reference to Pieris Brassicae L.(Lepidoptera: Pieridae) - Mtambo, Christine C (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Sc. Agric.) -- University of Stellenbosch, 1997.